Pengaruh Experiential Marketing Terhadap Kepuasan Pelanggan 3point Garden Cafe Bangkalan - Istiana Istiana; Nirma Kurriwati (Jurnal Kajian Ilmu Manajemen (JKIM), 2021)
The research aims to determine Experiential marketing which consists of sense, feel, think, act, relate to customer 3Point Garden Cafe Bangkalan. Sampling in this study used purposive sampling and analyzed using multiple linear regression analysis. The results of this study indicate that experiential marketing which consists of sense, feel, think, act, relate has a simultaneous effect on customer loyalty, and the variables have a partially significant effect on customer satisfaction.